Non-coding RNAs: The Neuroinflammatory Regulators in Neurodegenerative Diseases - Jiang, Hao; Zhang, Ying; Yue, Juan; Shi, Yuchen; Xiao, Bo; Xiao, Wenbiao; Luo, Zhaohui (Frontiers in Neurology, 2022)
As a common clue of nervous system diseases, neuroinflammation has attracted more and more attention, especially in the process of a variety of neurodegenerative diseases, such as Alzheimer's disease and Parkinson's disease. Long non-coding RNAs (lncRNAs) and microRNAs (miRNAs), two types of non-coding RNAs (ncRNAs), are widely involved in the process of neuroinflammation in neurodegenerative diseases. However, there is no review to systematically summarize that lncRNAs and miRNAs regulate neurodegenerative diseases through neuroinflammatory mechanisms. In this review, we summarize four main mechanisms of lncRNAs and miRNAs involved in neuroinflammation in neurodegenerative diseases, including the imbalance between proinflammatory and neuroprotective cells in microglia and astrocytes, NLRP3 inflammasome, oxidative stress and mitochondrial dysfunction, and inflammatory mediators. We hope to clarify the regulatory mechanism of lncRNAs and miRNAs in neurodegenerative diseases and provide new insights into the etiological treatment of neurodegenerative diseases from the perspective of neuroinflammation.